Fostering New Roles for Librarians: Skills Set for Repository Managers — Results of a Survey in Italy - Cassella, Maria; Morando, Maddalena (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
The open access movement in scholarly communication has grown considerably over the last ten years and it has driven an increase in the number of institutional repositories (IRs). New professional roles and skills had to be developed to secure effective IR management. Collection developmente expertise and metadata curation are regarded as strategic roles for repositories and therefore it is only logical for the library and information community to take on the responsibility for managing these digital archives. However, it has become clear that traditional librarian skills do not suffice anymore to run successful repositories. A richer set of skills is needed, including management and communication skills, technical skills, and expertise with regard to access rights and preservation of digital content. Referring to the work carried out by the SHERPA Project in the UK with regard to the skills set for repository staff, the authors performed a survey among repository managers in Italy to assess the educational and professional background of the repository managers and the skills set required to implement successful institutional repositories. The survey findings show that the professional profile of the repository manager is a multiform and complex one. It requires cross-functional and highly specialised competencies. Italian repository managers are of the opinion that the skills required to promote the repository within the institution and those required to deal with copyright issues as the most essential skills repository managers should acquire and be trained for. Collection development and metadata expertise, familiarity with project management and expertise in repository workflow design are also highly rated. Technical skills are needed to deal with interoperability standards and protocols. In Italy academic curricula do not meet the repository managers’ educational needs. Academic programmes should be developed to include communication, project management and team work skills and pay more attention to copyright issues. Until that time repository managers will have to spend a considerable part of their working lives on professional training and self-directed learning.